Peran E-Catalog dan CRM dalam Meningkatkan Minat Konsumen pada Layanan dan Produk Industri Farmasi - RM Haris Munandar; Dewi Fadila; Sari Lestari Zainal Ridho (Jurnal Ilmu Manajemen, 2025)
This study aims to develop a Digital Flipbook marketing media for home care services in pharmaceutical companies. The COVID-19 pandemic has changed consumer behavior, now paying more attention to health and relying on digital-based services. This study uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to design online information literacy. This study also uses quantitative methods, such as survey techniques through questionnaires. The population of the study was users of home care services in Palembang City. Data were analyzed using SEM-PLS to test the relationship between promotion through e-catalogs, customer service management, and purchase interest. The study results indicate that Digital Flipbook is an effective digital marketing media in increasing consumer knowledge and interest in-home care services. The evaluation was carried out through a consumer survey on the perception of using this Flipbook as a means of communication.